Dicianodiamida (DCD) como inibidor da nitrificação do nitrogênio amoniacal de dejetos líquidos de suínos no solo - Stüker, Fernanda (2010)
Inhibition of nitrification of ammonia nitrogen (N) from pig slurry in soil after application can mitigate N losses by denitrification and leaching of nitrate (NO3-), with economic and environmental benefits. However, this strategy has not yet been evaluated by Brazilian research, which motivated the present work. The objective was to evaluate the efficiency of the product AGROTAIN Plus, which contains 81% of the inhibitor dicyandiamide (DCD), in slowing the nitrification of ammonium N applied to soil with pig slurry. For this, two incubations were performed under controlled humidity (80% cc) and temperature (25ºC), where nitrification was assessed by the accumulation of NO3 - in soil. In the first incubation conducted for 72 days, doses of 3.5, 7.0 and 14 kg ha-1 of AGROTAIN Plus were compared, applied to the soil at the time of the manure addition (29.4 m3 ha-1). The dicyandiamide (DCD) inhibited the nitrification of N ammonia from manure, and the size and duration of this inhibition was dependent on the dose of AGROTAIN Plus applied. At a dose of 14 kg ha-1 (11.3 kg DCD ha-1) nitrification was completely inhibited in the first 12 days. During the first month after the manure application, where nitrification was more intense, increasing the dose of AGROTAIN Plus in 1 kg ha-1 (0.81 kg DCD ha-1) reduced the N-NO3 - accumulation in 3,8 kg ha-1. In the second incubation, evaluated for 60 days, was studied the effect of these same three doses of AGROTAIN Plus on soil microbial activity. Besides that, was evaluated the effect of the 7.0 kg ha-1 dose of product in inhibiting nitrification of N ammonia from pig slurry (34 m3 ha-1) and the mineralization of pig slurry C and N. The effect of the nitrification inhibitor was similar to that observed in the first incubation, while the manure N mineralization and soil microbial activity were not affected by the AGROTAIN Plus addition. The findings suggest that dicianodiamida (DCD), by delaying the onset of N-NO3 - in soil after application of pig slurry, reduces the N losses and the polluting potential of slurry.